Orange Is The New Blue? Case study of four Orange County constituencies that were won over by the Democrats in 2018 - Tomaszewski, Norbert (Political Preferences, 2022)
The 2018 midterm elections brought many surprises when talking about election results on Congressional level. One of them was definitely Democrats picking up four seats in the Orange County, which for many years was a Republican heartland in California. What happened? Was this just a one-time thing or a sign of blue wave in Donald Trump's era? The four case-studies of Democratic political campaigns will not only try to answer these questions, but also predict how should Republicans respond taking the example of 2020 elections.